Seagrass Meadows Provide 3D Habitat for Reef Fish - Serrano, Oscar; Serrano, Eduard; Inostroza, Karina; Lavery, Paul S.; Mateo, Miguel A.; Ballesteros, Enric (Frontiers in Marine Science, 2017)
Seagrass canopies typically provide a relatively flat habitat on the seabed, but seagrasses in the genus Posidonia can form organic-rich deposits known as mats. Erosional processes can scour channels through the mats, resulting in the formation of escarpments with caves. Here we report that caves within escarpments supported abundant reef fish assemblages, primarily by groupers. The characteristics of the cavities were highly variable, ranging from small-elongated holes to deep caves with large entrances. The origin of these caves (biological and/or geological) is unknown, but it is possible that fish behavior enhanced their formation. Posidonia seagrass escarpments provide a complex 3D habitat for reef fish that is not provided by typical canopy structure of seagrass. Further studies are required to gain insights into the natural history of seagrass escarpments and their ecological importance.